A fluorescent probe assay (Heparin Red) for direct detection of heparins in human plasma - Warttinger, Ulrich; Giese, Christina; Harenberg, Job; Holmer, Erik; Krämer, Roland (Analytical and bioanalytical chemistry, 2016)
Heparins are widely used anticoagulant drugs. The current monitoring practice for heparin in plasma, such as the chromogenic anti-factor Xa assay, relies on heparin-triggered activation of antithrombin, an inhibitor of coagulation proteases. Such assays are not applicable to the detection of non-anticoagulant heparins, an emerging class of drug candidates for therapeutic applications unrelated to anticlotting activity. This study describes the application of a commercially available fluorescent probe assay (Heparin Red) for the direct and sensitive detection of the “chemical” heparin in plasma, independent of any anticoagulant activity. The quantification range is about 0-5 μg/mL for both unfractionated heparin (corresponding to 0-1 IU/mL) and the low molecular weight heparin enoxaparin. The Heparin Red assay is of particular value for the quantification of non-anticoagulant heparins, as exemplified by the low molecular weight heparin derivative tafoxiparin and a N-desulfated-N-reacetylated heparin. Heparin octa- and decasaccharides are also detected. Open image in new window Graphical abstract Heparin quantification in plasma by mixing the sample with the Heparin Red reagent and fluorescence readout